2020
DOI: 10.4111/icu.20200084
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Gleason score distribution and Prostate Health Index in patients with prostate-specific antigen values of 2.5–10 ng/mL

Abstract: Purpose To determine the clinical significance and correlation between the Prostate Health Index (PHI) and Gleason score in patients with a prostate-specific antigen (PSA) value of 2.5–10 ng/mL. Materials and Methods This retrospective analysis included 114 patients who underwent biopsy after completion of the PHI from November 2018 to July 2019. Various parameters such as PSA, PHI, PSA density, free PSA, p2PSA, and %free PSA were collected, and correlations with biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Collectively, supporting data suggest that considering sensitivity and diagnostic accuracy by mpMRI study for PCa, implementing models such as multivariate might decrease the number of biopsies by 5% compared with mpMRI approach. This in concordance with Korean study from Choi et al [ 7 ], correlates the diagnostic accuracy of CSPCa detection could be increased when prostate biopsy is assessed in patients with a Prostate Health Index (PHI) ≥36.0. Interestingly, their study from Samsung Medical Center (Seoul, Korea) revealed that there was a clear Gleason score difference when the PHI cutoff value was set to 27.0 or 36.0 summarizing PHI is an additional tool that can be used as a selection criteria for biopsy, especially in patients with a PSA value ranging from 2.5 and 10 ng/mL [ 7 ].…”
supporting
confidence: 90%
“…Collectively, supporting data suggest that considering sensitivity and diagnostic accuracy by mpMRI study for PCa, implementing models such as multivariate might decrease the number of biopsies by 5% compared with mpMRI approach. This in concordance with Korean study from Choi et al [ 7 ], correlates the diagnostic accuracy of CSPCa detection could be increased when prostate biopsy is assessed in patients with a Prostate Health Index (PHI) ≥36.0. Interestingly, their study from Samsung Medical Center (Seoul, Korea) revealed that there was a clear Gleason score difference when the PHI cutoff value was set to 27.0 or 36.0 summarizing PHI is an additional tool that can be used as a selection criteria for biopsy, especially in patients with a PSA value ranging from 2.5 and 10 ng/mL [ 7 ].…”
supporting
confidence: 90%
“…Thus, 27 might not be the ideal cut‐off when discriminating csPCa from iPCa or no PCa. Nevertheless, a PHI value of 27 was reported in several clinical studies either as cut‐off or as upper limit of a low‐risk range in relation to csPCa 9,24–26 …”
Section: Discussionmentioning
confidence: 99%
“…Three of these could not be retrieved [17] , [18] , [19] . Sixty-five studies [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , reported in 69 articles [20] , [21] ,…”
Section: Evidence Synthesisunclassified
“…TRUS-guided prostate biopsy from 10 to 12 cylinders 2. Elevated PSA (2.00–20.00 ng/ml) NR Caucasians Asians 2.00–10.00 d 2.00–10.00 d Choi (2020) [61] 114 37 28 Gleason ≥7 62.81 a 7.87 a NR 1. Biopsied with previous PSA and PHI 2.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation